Revisiting the role of Annexins in membrane trafficking - Thomas Grewal; Volker Gerke; Jesper Nylandsted; Carles Rentero; Carlos Enrich (Cellular and Molecular Life Sciences)
Abstract Ever since their discovery five decades ago, annexins have been implicated in membrane-related events along endo- and exocytic pathways. Over the years, structural, biochemical and cell imaging studies have revealed that annexins facilitate the organization of membrane domains to allow the formation of tight interactions between membranes destined to fuse. Yet, a comprehensive understanding that would elucidate the molecular characteristics, specific pathways and modes of action in relation to membrane trafficking events for all 12 human annexins is still lacking. By and large, annexins are considered cytosolic proteins that bind to acidic membrane phospholipids upon Ca²⁺ elevation. However, as extended Ca²⁺ stores in the ER, mitochondria and lysosomes continuously exchange Ca²⁺ with the cytosol, significant amounts of annexins remain in contact with membranes for the majority of their intracellular lifespan. Hence, how annexins sense and respond to subcellular Ca2+ fluctuations in a dynamic manner and how this influences their localized lipid-binding preferences and functions still needs further clarification. This review examines earlier and recent observations that highlight the involvement of annexins in membrane traffic at the crossroads of endo- and exocytic pathways. The role of annexins in those less known facets such as membrane contact site formation, membrane repair, exosome biology and membrane-less compartments including annexins as RNA-binding proteins will also be discussed. Together, these new avenues strongly imply that annexins serve as important regulators of membrane trafficking.